Islamic Ethics and the Genome Question - Ghaly, Mohammed (Studies in Islamic Ethics, 2018)
Islamic Ethics and the Genome Question is one of the first academic works, which examine the field of genomics from an Islamic perspective. The contributions in the volume also accommodate and interact with critical insights from outside the Islamic tradition. Readership: Researchers and students specialized in ethics, bioethics and Islamic studies. Additionally, this volume will be a source of important information for geneticists, genomicists and social scientists who are interested in the ethical discourse about genomics in the Muslim world.